Pearl and Wagner : Three Secrets - McMullan, Kate; Alley, R. W. (Robert W.) (New York : Dial Books for Young Readers, 2004)
Pearl and Wagner, a rabbit and a mouse who are best friends, learn about secrets during a trip to an ice cream factory and an amusement park birthday party.
"Dial Easy-to-Read."
Keywords: Ice cream, ices, etc. -- Fiction; Amusement parks -- Fiction; Secrets -- Fiction; Birthdays -- Fiction; Rabbits -- Fiction; Mice -- Fiction